Decoupling Between Diastolic Pulmonary Artery and Pulmonary Capillary Wedge Pressures Is Associated With Right Ventricular Dysfunction and Hemocompatibility‐Related Adverse Events in Patients With Left Ventricular Assist Devices. Issue 7 (9th April 2020) - Imamura, Teruhiko; Narang, Nikhil; Kim, Gene; Raikhelkar, Jayant; Chung, Ben; Nguyen, Ann; Holzhauser, Luise; Rodgers, Daniel; Kalantari, Sara; Smith, Bryan; Ota, Takeyoshi; Song, Tae; et al.
Abstract : Background: Decoupling between diastolic pulmonary artery pressure and pulmonary capillary wedge pressure is an index of pulmonary vascular damage. This study assessed the impact of decoupling on right heart function and hemocompatibility‐related adverse events. Methods and Results: In this prospective study, patients underwent invasive hemodynamic tests following left ventricular assist device implantation. Decoupling was defined as a difference of >5 mm Hg between diastolic pulmonary artery pressure and pulmonary capillary wedge pressure. Among 92 patients with left ventricular assist devices (median age, 61 years; 57% male), 44 patients (48%) had decoupling. Right heart function and size by echocardiographic assessment worsened during a 1‐year observational period in the decoupling group as compared with the control group ( P <0.05). The decoupling group had significantly lower 1‐year freedom from any hemocompatibility‐related adverse events (49% versus 79%; P =0.005), as well as a higher hemocompatibility score (2.14 versus 0.67; P =0.004). The scoring system depicts the severity of hemocompatibility‐related adverse events using 4 escalating tiers. Increased tier I scores (1–2 gastrointestinal bleedings or medically managed pump thrombosis; P =0.027) and tier IIIB scores (disabling stroke or hemocompatibility‐related adverse event–related death; P =0.041) occurred more frequently in the decoupling group. Conclusions: The presence of decoupling between diastolic pulmonary artery pressure and pulmonary capillary wedge pressure was associated with worsening of right heart function and hemocompatibility‐related adverse events in patients with left ventricular assist devices.